INTERACTIVE SOCIAL MEDIA STRATEGY TO INCREASE ENGAGEMENT AT SD PERUMNAS 1 - Andi Ratu Ayuashari Anwar; Sriwidayani Syam; By Tri Agung Nusantara Kr. J Tompong (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The growing intensity of social media usage within society has encouraged educational institutions to adopt digital platforms as strategic tools for promoting their services and building effective communication with prospective students and parents. This study aims to examine the use of interactive social media marketing strategies at SD Perumnas I, with a focus on the effectiveness of these platforms in enhancing engagement, as well as the challenges encountered by the school. A qualitative approach was employed, involving field observation, in-depth interviews with two key informants (a classroom teacher and the school’s social media administrator), and document analysis. The findings reveal that since the COVID-19 pandemic, the school has utilized platforms such as WhatsApp, Instagram, and TikTok for communication and promotion. WhatsApp was considered the most effective for direct interaction with parents, while Instagram and TikTok were more successful in reaching broader audiences through visual content such as school activity videos and photos. However, several obstacles were identified, including infrequent content posting, limited creativity, and insufficient training for teachers in managing digital media. Internally, the school supports these efforts by providing Wi-Fi access and encouraging personalized approaches through WhatsApp groups. This study concludes that the success of social media-based school marketing strategies depends on content consistency, technical skills, and the relevance of information presented. Therefore, improving teachers’ capacity in digital branding and content management is essential to support effective social media promotion in primary education settings.